TRANSFER OF MARKETING KNOWLEDGE IN THAI INTERNATIONAL JOINT VENTURE FIRMS - Osman Mohamad,; T. Ramayah,; Nit Hathaivaseawong, (Asian Academy of Management Journal, 2010)
The focus of this study is the transfer of marketing knowledge within Thai joint venture firms. The perspectives of Thai managers were surveyed using a structured instrument. The analysis identifies seven dimensions of marketing management knowledge: promotion management, price management, logistics management, product innovation management, strategic marketing management, cross-cultural management, and target marketing management. The incidence of transfer is highest for activities in strategic marketing management, followed by price management. Transfer in product innovation management and target marketing management tends to vary with the age of the joint venture. Joint venture firms with foreign partners originating from Western, advanced, industrialised nations recorded the highest incidence of knowledge transfer occurring within product innovation management. This trend also holds true for the management of promotion activities. The incidence of transfer in target marketing management is lowest among firms with foreign partners from neighbouring nations. The incidence of knowledge transfer within product innovation and target marketing also tends to vary with the age of the joint venture. An analysis based on industry classification revealed that the transfer of knowledge regarding logistics management occurs most for firms in the manufacturing sector. In the service sector, the highest incidence of knowledge transfer within the areas of promotion management and target marketing management occurred in the agricultural sector.